PENGARUH REKRUTMEN DAN PENEMPATAN KERJA TERHADAP KINERJA PEGAWAI TENAGA HARIAN LEPAS DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN BANYUASIN - Ulandari, Hesi; Heriyanto (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to determine the effect of recruitment and job placement on the performance of daily freelance employees of the Banyuasin Regency Education and Culture Office. This research is a quantitative study using the SPSS Statistics 27 program application. The analysis technique used is classical assumption analysis techniques such as normality test, multicollinearity test, heteroscedasticity test and multiple linear regression analysis. The population in this study were 135 casual daily labor employees. Sampling using simple random sampling technique using the Yamane formula with a sample of 101 respondents. The results showed that simultaneously the Recruitment and Job Placement variables jointly influenced the performance variables of daily freelance employees of the education and culture office of the banyuasin district. As well as partially obtained the results that the recruitment and job placement variables have a significant effect on the performance variables of casual daily employees of the education and culture office of the banyuasin district. And the Recruitment and Job Placement variables together (simultaneously) affect the performance variable of daily freelance employees of the education and culture office of the banyuasin district.